EVALUATION OF REGIONAL WAGE CONVERGENCE IN POLAND - Ferens, Ewa (Acta Scientiarum Polonorum. Oeconomia, 2015)
The aim of this paper is to present and analyze the regional differentiation of nominal wages in Section A of Polish classification of business activities (PKD) and in the entire economy in Poland in the years 2005-2013 and to examine whether there is a convergence or divergence process in the level of this wages. The results show that in spite of gradual wage growth in all voivodships, the regions do not converge in this term. In case of nominal wages in agriculture sector, a slight beta convergence is observed.